A decade of change in mainstream education for children with intellectual disabilities in the Republic of Ireland. Issue 1 (2nd January 2016) - McConkey, Roy; Kelly, Caraoisa; Craig, Sarah; Shevlin, Michael
Abstract: Inclusive rather than segregated schooling has been advocated in several significant international declarations during the past two decades. Even so children with significant intellectual disabilities are at greater risk of being excluded from mainstream education, unless particular efforts are made to support them in such settings. These children and young people are more likely to be educated in special schools or in special classes within mainstream schools. In the decade from 2003 to 2013, the Republic of Ireland enacted legislation and provided additional financial resources for pupils with special educational needs, although these were more constrained during the financial crisis that Ireland experienced from 2008 onwards. A national database, updated annually, is maintained of children receiving services from specialist intellectual disability services and this enabled comparisons to be made for the enrolments of over 8000 children aged 4–19 in mainstream and special schools following the introduction of legislation and availability of additional resources. The data showed a steady increase in children with significant intellectual disabilities attending mainstream classes and a decrease in the proportion attending special schools along with a much smaller but decreasing proportion in special classes. The profile of pupils with intellectual disabilities in mainstream and special schools also changed over the 10 years with higher proportions of males, of pupils with moderate disabilities and those of primary age attending mainstream schools, whereas special schools now tend to have higher proportions of females and those of secondary school age. However, there was marked regional variation in the proportions of pupils in mainstream schools which was attributed to the availability of special schools across the State. This study demonstrates how a national data-set can be used to track the impact that policy changes and legislation designed to enhance the development of inclusive learning environments had on the number of pupils availing of mainstream opportunities. It was also possible to identify prevailing trends in types of support provided within schools and the changing pattern of provision for pupils with different levels of intellectual disability. At the broader level of international trends in policy and provision aimed at establishing inclusive learning environments, this study demonstrates the need for a common frame of reference around which the national and international conversations on educational systems can take place.